The IL-33 gene is related to increased susceptibility to systemic sclerosis - Koca, Suleyman Serdar; Pehlivan, Yavuz; Kara, Murat; Alibaz-Oner, Fatma; Oztuzcu, Serdar; Yilmaz, Neslihan; Onat, Ahmet Mesut (Springer Heidelberg, 2016)
Systemic sclerosis (SSc) is a chronic inflammatory disease characterized by widespread fibrosis of the skin and several visceral organs. The pro-fibrotic potential of interleukin (IL)-33 has been demonstrated by in both in vitro and in vivo settings; moreover, increased level of IL-33 has also been reported in patients with SSc. Therefore, the aim of the present study was to detect the potential association of IL-33 gene polymorphisms on the susceptibility of SSc. A total of 300 SSc patients and 280 healthy controls (HC) were enrolled in this multicentric preliminary candidate gene study. DNA samples were harvested using an appropriate commercial DNA isolation kit. Four single nucleotide polymorphisms (SNPs) of IL-33 gene (rs7044343, rs1157505, rs11792633 and rs1929992) were genotyped using the appropriate commercial primer/probe sets on real-time PCR. There was no significant difference in terms of the allelic distributions and minor allele frequencies of evaluated four IL-33 polymorphisms between the SSc and HC groups (P > 0.05 for all). Moreover, the genotypic distributions of rs1157505, rs11792633 and rs1929992 polymorphisms were not significantly different (P > 0.05 for all). However, CC genotype of rs7044343 SNP was significantly higher in the SSc group compared to the HC group (P = 0.013, OR 1.75, 95 % CI 1.12-2.72). This preliminary candidate gene study demonstrates that rs7044343 polymorphism of IL-33 gene is associated with the susceptibility to the SSc in Turkish population. It may be suggested that IL-33 gene may be a candidate gene to research in SSc.
Keywords: Systemic sclerosis; Genetic; IL-33 gene polymorphism